2015
DOI: 10.1089/mdr.2015.0032
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Acinetobacter baumannii Infections in Critically Ill Patients with Cancer: A Matched Case–Control Study

Abstract: AB infections in critically ill cancer patients were independently associated with increased mortality and increased ICU LOS. Measures to improve the outcomes of critically ill cancer patients infected with AB are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
3
24
2
Order By: Relevance
“…Previous studies have highlighted on the importance of a patient's immune status on the outcome, with prolonged LOS and mortality rates, particularly when a hematological malignancy is present (Nazer et al, 2015; Gu et al, 2016). Though we did not find any significant association between malignancies and mortality, exposure to high dose steroids increased the risk of dying by 7.4-folds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted on the importance of a patient's immune status on the outcome, with prolonged LOS and mortality rates, particularly when a hematological malignancy is present (Nazer et al, 2015; Gu et al, 2016). Though we did not find any significant association between malignancies and mortality, exposure to high dose steroids increased the risk of dying by 7.4-folds.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hospitalized patients were at increased risk for colonization with AB (90%; P=0.026) when compared to outpatients (10%) with A. baumannii (Table 3). Recent studies from Jordan and other countries reported that A. Baumannii frequently colonizes hospitalized patients, causing sporadic invasive infection and nosocomial outbreaks, especially among critically ill patients and in ICUs [2,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that the majority of A. baumannii species isolates were resistant in the range between 76% to 100% to commonly useful antimicrobial agents in the treatment of gram-negative infections, including infections due to A. baumannii (Table 4). Previous studies which has been performed over the last few years at the Jordan University Hospital and KHCC in Amman, have also found that the majority of A. baumannii isolates from patients and hospital environment sources was also multidrug resistant [2,3,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations